Journalist, Spy, Propagandist: About Vándory Lajos and His Activity in Romania (1876–1885) - GHENGHEA, Mircea-Cristian (Studia Universitatis Babeș-Bolyai Historia, 2024)
Towards the end of the 19th century, the relations between Austria-Hungary and Romania experienced several delicate episodes, caused by the diametrically opposed interests of the two sides regarding the specific realities of South-Eastern Europe. The rulers in Vienna and especially those in Budapest could only see the Romanian state as an obstacle to their plans, and therefore tried to quickly learn and decipher the diplomatic and political intentions and initiatives of the Romanian decision-makers. On different occasions, in order to obtain the necessary information, they resorted to setting up and supporting networks of influencers, propagandists and spies, both in Transylvania and across the Carpathians. The present article aims to add details to the depiction of an interesting figure, Vándory Lajos, who, according to the press of the time and several archival documents, was one of those who operated within the territory of the Romanian state as a spy, under the cover of working as a journalist. At various times, by his actions, he contributed to the further straining of the already problematic Romanian-Hungarian relations. Rezumat: Spre sfârşitul secolului al XIX-lea, relaţiile dintre Austro-Ungaria şi România au cunoscut mai multe episoade delicate, provocate de interesele diametral opuse ale celor două părţi cu privire la realităţile specifice sud-estului Europei. Conducătorii de la Viena şi mai ales de la Budapesta nu puteau vedea în statul român decât un obstacol în calea planurilor lor, încercând, în consecinţă, să cunoască şi să descifreze cât mai repede intenţiile şi iniţiativele diplomatice şi politice ale factorilor decidenţi din România. Pentru obţinerea informaţiilor necesare, au făcut apel în diverse rânduri la constituirea şi sprijinirea unor reţele de agenţi de influenţă, propagandişti şi spioni, atât în Transilvania, cât şi peste Carpaţi. Prin intermediul textului nostru, încercăm să contribuim la completarea imaginii unui interesant personaj, Vándory Lajos, care, aşa cum arată presa vremii şi documentele de arhivă, a fost unul din cei care au activat pe teritoriul statului român în calitate de spion, sub acoperirea îndeletnicirii de gazetar. În diferite momente, prin acţiunile sale, a contribuit la tensionarea suplimentară a relaţiilor româno-maghiare, oricum problematice. Cuvinte-cheie: Vándory Lajos, relaţii româno-maghiare, presă, propagandă, spionaj. Article: history; Received: 08.10.2023; Revised: 30.10.2023 Accepted: 01.11.2023; Available online: 30.01.2024